Micro and Macro Pattern Analyses of fMRI Data Support Both Early and Late Interaction of Numerical and Spatial Information - Koten, Jan W.; Lonnemann, Jan; Willmes, Klaus; Knops, André (Frontiers in Human Neuroscience, 2011)
Numbers and space are two semantic primitives that interact with each other. Both recruit brain regions along the dorsal pathway, notably parietal cortex. This makes parietal cortex a candidate for the origin of numerical spatial interaction. The underlying cognitive architecture of the interaction is still under scrutiny. Two classes of explanations can be distinguished. The early interaction approach assumes that numerical and spatial information are integrated into a single representation at a semantic level. A second approach postulates independent semantic representations. Only at the stage of response selection and preparation these two streams interact. In this study we used a numerical landmark task to identify the locus of the interaction between numbers and space. While lying in an MR scanner participants decided on the smaller of two numerical intervals in a visually presented number triplet. The spatial position of the middle number was varied; hence spatial intervals were congruent or incongruent with the numerical intervals. Responses in incongruent trials were slower and less accurate than in congruent trials. By combining across vertex correlations (micro pattern) with a cluster analysis (macro pattern) we identified three networks that were devoted to number processing, eye movements, and sensory motor functions. Using support vector machine classifiers in different regions of interest along the IPS, the frontal eye fields and supplementary motor area to distinguish between congruent and incongruent trials we were able to distinguish between congruent and incongruent trials in each of the three networks. We suggest that the three identified networks participate in the integration of numerical and spatial information and that the exclusive assumption of either an early or a late interaction between numerical and spatial information does not do justice to the complex interaction between both dimensions.